Preparedness and Participation in Disaster Risks Mitigation among Public Elementary Schools of 3rd District in Zamboanga del Norte - Napallaton, Marife; Antone, June Michael (JPAIR Multidisciplinary Research, 2019)
As reported in the early days of November 2013, more than 6,000 people died, millions of people were displaced and affected in the central part of the Philippines which were hit by Typhoon Yolanda which would enter into historical records and the minds of people in the Philippines. Thus, every individual must be aware of the importance of knowing the nature of this disaster. This study aimed to determine the natural and man-made disasters that occurred and was experienced by the elementary schools’ faculty, staff, and the LDRRMC personnel of the selected areas of Leon B. Postigo, Godod, Salug, Liloy, Gutalac, Kalawit, Tampilisan and, Lebanon, Zamboanga del Norte. The level of preparedness and participation of these municipalities are at risk by the Local Disaster Risk Reduction, and Management plans were determined as prescribed by the R.A.10121. Respondents considered by random sampling were from the local government units, particularly the faculty and staff of the elementary schools of the 3rd district. A self-made questionnaire checklist was used in gathering the data. Findings disclosed that earthquake, flood, vehicular, and fire incidents appeared as the most prevalent. They lacked monitoring and thorough implementations of the programs prescribed by the NDRRMC. They purchased some important facilities, however, some necessary equipment was not procured and people are less participative in mitigating disaster risk reduction.